La suspensión en el foro de abogados en multas impuestas por el Consejo de la Judicatura y la vulneración al principio de proporcionalidad - Medina Garces, Daniel Stalyn (2023)
ABSTRACT: In order to define the problem, it is pertinent to bring up what is provided in Article 336 of the General Organic Code of Processes, which rules that when defaulting for a period of three months for the payment of fines that have been imposed by judges or the Council of the Judiciary, causes the suspension of the lawyers' forum, which subsists until the payment is made. Said norm is presumed to affect the principle of proportionality, the same one that is found within the guarantees of due process based on Article 76.6 of the Constitution. The quantitative approach to research is a form of research that focuses on numerical data. This form of research is used to study large-scale phenomena, analyze patterns and trends, and predict outcomes. It has a statistical approach, using techniques such as surveys, experiments, and regression analysis to collect and analyze data. The quantitative approach is a systematic and structured approach. It is the most common form of inquiry used in the field of social science and research. It is concluded that according to Art.336 of the Organic Code of the Judiciary, it is established that failure to pay the fine imposed by the Council of the Judiciary, within a period of three months, will cause the suspension in the forum of lawyers. However, this measure violates the principle of proportionality in administrative sanctions according to Art.76.6 of the Constitution of Ecuador. Keywords: suspension; principle of proportionality; lawyers forum; harmful